BEING AN ENGLISH DEBATING COACH: A TEACHER’S ROLES AND PROFESSIONAL IDENTITY CONSTRUCTION - Atin Kurniawati (Universitas Islam Nahdlatul Ulama Jepara, 2022)
English debating has taken its role to improve students’ performance in speaking and critical thinking skill, but it is through a long and uneasy process. This paper aims at exploring the lived experience of an English teacher in an Islamic boarding school who initiated the first English debating club and coached the members to be a considerable debating team in regional and national levels. The data of this narrative inquiry study were collected through several semi-structured interviews. The meaningful experiences and insights from the research data were highlighted thematically and presented as the data findings. This study found several roles of the teacher in initiating the debating club, such as establishing the club, recruiting the members, structuring the regular rehearsal, mapping the students’ strengths and weaknesses, and giving feedback and motivation. Under the limited sources of time and information, the teacher guided the students to work effectively and support them mentally. Her roles in coaching the debating club also inspired her professional identity as an English teacher. It implied that establishing running an English debating community requires a sequence of roles. In another way, it also strengthened the English teacher’s professional identity. Implications and practical suggestions are also discussed in this paper.